Northern Fergana hills and their features - Mirzamakhmudov Odiljon Tukhtasinovich; Tukhtasinov Mirzaolim Odiljon ugli (Genius Journals, 2023)
The article discusses the natural-geographic conditions of the Northern Fergana hills and the factors that create them. The meaning of the term “adyr”, geological, tectonic, geomorphological structure, climate, ground and surface waters, soils, representatives of the flora and fauna of the Northern Fergana adyrs.
Keywords: valley; Northern Fergana; geological structure; deposits